The Influence of Digital Influencers on Brand Image in the Lifestyle Product Market: A Bibliometric Analysis - Muhammad Aditya, (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
Abstract. This study conducts a bibliometric analysis to assess how digital influencers impact brand image within the lifestyle product market. As influencer marketing continues to grow, understanding the role of influencers in shaping consumer perception and brand identity is increasingly essential. This analysis synthesizes existing academic contributions on the influence of digital influencers, highlighting key themes such as credibility, trust, and audience engagement. The findings indicate that influencer marketing effectively supports brand-building by fostering consumer emotional attachment, reinforcing brand identity, and influencing purchasing decisions. Additionally, the analysis identifies gaps in the current literature and offers recommendations for marketers on leveraging influencer marketing to enhance brand visibility in a highly competitive lifestyle sector.